INVESTIGATING ALTERNATIVE RESOURCES FOR ENGLISH LANGUAGE TEACHING AND LEARNING - Elih Sutisna Yanto (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2014)
It is unquestionable that the availability of English language teaching and learning resources is often associated with the financial ability of an institution. Consequently, teachers at new institutions rarely enjoy vast resources. At Department of English Education, Faculty of Teachers Training and Education Unsika, for example, recent materials and ICT equipment are scarcely available. To cope with such conditions, teachers have to be creative and innovative. In this paper, we describe how teachers can cope with limited resources by utilizing free resources and networking. We also propose a triangle concept in which teachers, students and the management work together to cope with limited resources. A teacher has to move from simply a planner of lessons and a transmitter of knowledge to a facilitator of communication. Students have to be encouraged to be autonomous in learning. And, the management has to be informed about the selection of beneficial and affordable resources for English language teaching and learning.Keyword: Investigating Alternative Resources, Teaching, Learning